Psychosocial Burden Due to Acne Vulgaris Affects Treatment-Seeking Behavior in Medical Students in Jakarta, Indonesia - Franklind Matthew (Universitas Padjadjaran, 2021)
Background: Acne vulgaris (AV) is a chronic inflammation of the pilosebaceous unit of the skin that occurs in 85% of adolescents and can continue into adulthood. The skin of the facial area has an essential role in socializing, therefore, facial AV can contribute to the accumulation of psychosocial stress. The prevalence of individuals with AV seeking treatments is low in some countries. This study aimed to determine the association between psychosocial burdens due to AV and medical treatment-seeking behavior in young adults.